2005
DOI: 10.1177/0885066604271619
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Multicenter Study to Evaluate the Feasibility and Safety of Aggressive Antihypertensive Treatment in Patients With Acute Intracerebral Hemorrhage

Abstract: The authors performed a multicenter prospective observational study to evaluate the feasibility and safety of intravenous antihypertensive protocol for acute hypertension in patients with intracerebral hemorrhage (ICH). Twenty-seven patients with ICH and acute hypertension (mean age 61.37 +/- 14.27; 10 were men) were treated to maintain the systolic blood pressure (BP) below 160 mm Hg and diastolic BP below 90 mm Hg within 24 hours of symptom onset. Neurological deterioration (defined as a decrease in initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 36 publications
2
88
1
1
Order By: Relevance
“…There is potential benefit of reducing rates of hematoma expansion with systemic blood pressure reduction versus the potential provocation of ischemia in the perihematoma region [24,30,31]. Recent data from pre-clinical and clinical studies have supported the relative safety of blood pressure reduction in acute intracerebral hemorrhage, although the benefit remains unclear [32,33]. Patients with subarachnoid hemorrhage remain at risk of second rupture acutely following an initial rupture of intracranial aneurysm [34].…”
Section: Discussionmentioning
confidence: 99%
“…There is potential benefit of reducing rates of hematoma expansion with systemic blood pressure reduction versus the potential provocation of ischemia in the perihematoma region [24,30,31]. Recent data from pre-clinical and clinical studies have supported the relative safety of blood pressure reduction in acute intracerebral hemorrhage, although the benefit remains unclear [32,33]. Patients with subarachnoid hemorrhage remain at risk of second rupture acutely following an initial rupture of intracranial aneurysm [34].…”
Section: Discussionmentioning
confidence: 99%
“…There was also no effect of treatment on clinical outcomes at 90 days [36]. Smaller, nonrandomized studies have also found that more aggressive BP lowering is associated with strong trends toward reduced hematoma enlargement [35][36][37][38][39].…”
Section: Blood Pressure Management In Ichmentioning
confidence: 96%
“…The mean arterial pressure should be maintained at or below 130 mm Hg for patients with ICH and a history of hypertension [206][207][208] . Keeping the systolic blood pressure in acute ICH below 160 mm Hg and diastolic below 90 mm Hg leads to the growth of hematoma in 9% of patients as compared with 38% of patients in a study where the primary target was not blood pressure measurement 190,209 . In patients with known prior hypertension or signs of chronic hypertension, based on limited data, an upper limit of blood pressure should be 180/105 mm Hg, and in patients without known hypertension, the upper recommended limit is 160/95 mm Hg 22 .…”
Section: Medical Treatment Blood Pressurementioning
confidence: 97%